Ni-based nanocluster-loaded silicon carbide catalyst for hydrogen production by electrolysis of water and preparation method thereof
Ni6 nanoclusters were prepared by wet chemistry and loaded to the SiC surface, which solved the problems of low efficiency and poor stability of existing non-precious metal catalysts in the electrocatalytic hydrogen production process, and achieved efficient and stable electrocatalytic hydrolysis hydrogen production performance.
Patent Information
- Application Number
- CN202411847772.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-12-16
AI Technical Summary
In the electrocatalytic hydrogen production process, existing non-precious metal catalysts have problems such as low catalytic conversion efficiency, complex synthesis process and low stability, making it difficult to achieve a stable and high conversion efficiency catalytic electrolysis hydrogen production process.
The cyclic Ni6 nanocluster was prepared by wet chemistry and loaded to the surface of silicon carbide (SiC). After the inexpensive raw material NaBH4 reduction treatment, Ni-based nanoclusters were prepared to produce a hydrogen production catalyst for silicon carbide electrolysis. This method is simple in conditions, has high safety and low cost, and can quickly and efficiently obtain uniformly loaded SiC electrocatalytic materials.
It achieves efficient and stable electrocatalytic hydrolysis hydrogen production performance, with high catalytic activity and good stability, providing a new strategy to prepare more Ni-based nanocluster-based electrocatalytic hydrogen production catalysts.
Smart Images

Figure CN119824457A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water electrolysis hydrogen production catalysts, and specifically relates to a Ni-based nanocluster-loaded silicon carbide water electrolysis hydrogen production catalyst and a preparation method thereof. Background Art
[0002] Electrocatalysis is considered to be an effective way to produce hydrogen with high energy conversion efficiency and zero greenhouse gas emissions. The performance of electrocatalytic hydrogen production catalysts largely affects the cost, output and stability of hydrogen production. In electrocatalytic hydrogen evolution, platinum (Pt) is one of the most commonly used catalysts due to its excellent electrochemical properties and catalytic activity, but its high cost and scarcity limit its industrial application.
[0003] Some non-precious metals such as nickel (Ni) and iron (Fe) are used to replace the precious metal Pt as catalysts for electrocatalytic hydrogen evolution reaction. Carbon-based materials such as carbon nanotubes and graphene are also studied as carriers of Pt substitutes to further reduce costs and improve electrocatalytic performance. Nickel is abundant in the earth's crust, has a lower cost than precious metals, and exhibits good catalytic activity in the process of water electrolysis. However, since its activity and selectivity are affected by factors such as crystal structure, surface characteristics, hydrogen adsorption capacity, alloying, etc., Ni exhibits variability, complexity, and poor durability in the catalytic process, which limits its application. Studies have shown that by controlling the morphology, size, and surface modification of nickel nanoparticles to regulate the distribution and density of active sites on the nickel surface, its catalytic activity and selectivity can be improved. In addition, by loading nickel on inert or active carriers, such as oxides, carbon materials, etc., its dispersion and stability can be increased. Current non-precious metal catalysts generally have problems such as low catalytic conversion efficiency, complex synthesis process and low stability. There is an urgent need to develop a simple and efficient synthesis method for non-precious metal catalysts to achieve a stable and high-conversion efficiency catalytic water electrolysis hydrogen production process. Summary of the invention
[0004] One of the purposes of the present invention is to provide a method for preparing a Ni-based nanocluster-loaded silicon carbide water electrolysis hydrogen production catalyst, the preparation method has simple conditions, high safety, low cost, high stability, high yield, and environmental friendliness, and the prepared catalyst has high HER catalytic activity and good stability.
[0005] To achieve the above object, the present invention adopts the following technical scheme: a method for preparing a Ni-based nanocluster-supported silicon carbide water electrolysis hydrogen production catalyst, comprising the following steps:
[0006] S1, dissolving Ni salt and tetraoctylammonium bromide TOAB in tetrahydrofuran (THF) at a mass ratio of 1:2-2:1 to form a dark blue solution; wherein the concentration of Ni salt in tetrahydrofuran is 0.004-0.01 g / ml;
[0007] S2, take 300ml of dark blue solution, add 4-6ml of toluenethiol PhCH 2 SH, stir thoroughly until all metal atoms are fully coordinated, slowly add borohydride solution or hydroxide solution until the solution turns gray, stop adding, and keep the reaction at 10±2℃ for 48-72h to obtain Ni 6 (SCH 2 Ph) 12 Dark brown solution of nanoclusters;
[0008] S3, the dark brown solution was filtered, and the filtered material was washed to obtain a crude product; the crude product was dissolved in a mixed solvent of methanol and THF in a volume ratio of 1:1 to form a cluster saturated solution, and placed in an air atmosphere until the solvent was completely evaporated to obtain a regular black hexagonal single crystal Ni 6 (SCH 2 Ph) 12 ;
[0009] S4, black hexagonal single crystal Ni 6 (SCH 2 Ph) 12 Dissolved in dichloromethane solution, then added SiC ultrasonic dispersion to obtain a mixed solution, black hexagonal single crystal Ni 6 (SCH 2 Ph) 12 The mass ratio of Ni to SiC is 1:(4-6); then the dichloromethane in the mixed solution is completely evaporated, the obtained solid is collected and ground to obtain Ni 6 / SiC;
[0010] S5. Ni 6 / SiC is added to a concentration of 0.35-0.45 mol / L NaBH 4 The solution was added in an amount of 2.5-4 mg / ml, and then ultrasonicated, separated, washed and dried to obtain a Ni-based nanocluster-supported silicon carbide electrolytic water hydrogen production catalyst, denoted as Ni 6 / SiC-H catalyst.
[0011] Further improvement of the preparation method of Ni-based nanocluster supported silicon carbide electrolysis water hydrogen production catalyst:
[0012] Preferably, the Ni salt is NiCl 2 6H 2 O.
[0013] Preferably, the borohydride solution is a sodium, potassium or lithium borohydride solution, and the hydroxide solution is a sodium, potassium or lithium hydroxide solution.
[0014] Preferably, the concentration of the borohydride solution or hydroxide solution is 0.9-1.1 g / ml.
[0015] Preferably, in step S3, the dark brown solution is filtered using absorbent cotton.
[0016] Preferably, in step S3, CH 2 Cl 2 The filtrate was washed with water to obtain a crude product.
[0017] Preferably, in step S4, the black hexagonal single crystal Ni 6 (SCH 2 Ph) 12 The solubility concentration in dichloromethane solution is 0.8-1.2 mg / ml.
[0018] Preferably, in step S4, the mixed solution is sealed in a rotary evaporator at 30-40° C. to completely evaporate the dichloromethane.
[0019] Preferably, in step S5, the product is separated by ultrasonication for 2-3 hours, centrifugation at 8000-10000 rpm for 3-5 minutes, washed four times with deionized water, and dried at 60-80° C. for 12-15 hours.
[0020] The second object of the present invention is to provide a Ni-based nanocluster-loaded silicon carbide electrolysis water hydrogen production catalyst obtained by the preparation method of any one of the above-mentioned Ni-based nanocluster-loaded silicon carbide electrolysis water hydrogen production catalysts.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1) The present invention has created a new type of highly efficient and stable Ni-based electrocatalytic hydrogen evolution catalyst and its preparation method, and prepared a cyclic Ni 6 Nanoclusters, and then cheap Ni-based nanoclusters are loaded onto the SiC surface, and then reacted with cheap raw material NaBH 4 The reduction treatment does not require high temperature, hydrothermal and other complex operations, and can quickly and efficiently obtain SiC electrocatalytic materials with uniform Ni cluster loading, which have efficient and stable electrocatalytic hydrolysis hydrogen production performance.
[0023] Nanocluster Ni 6 (SCH 2 PH) 12 During the preparation process, NiCl 2 6H 2 O and tetraoctylammonium bromide (TOAB) were dissolved in tetrahydrofuran (THF) to form a dark blue solution. Then toluenethiol (PhCH 2SH), the solution was stirred for more than 2 hours to ensure that all metal atoms were fully coordinated. Then 2 mL of 1 g / mL NaBH 4 The solution quickly turned gray. After the reaction was maintained at 10±2℃ for 48 hours, a dark brown solution was obtained, indicating that Ni 6 (SCH 2 Ph) 12 Synthesis of nanoclusters. The resulting solution was further filtered through cotton wool and CH 2 Cl 2 The organic phase was washed 3-5 times with water to remove the soluble byproducts and unreacted water-soluble precursors. By removing the solvent of the obtained organic phase, the isolated crude product of nanoclusters was obtained. 6 (SCH 2 Ph) 12 Single crystals of nanoclusters were prepared by dissolving the crude product into a 1:1 methanol and THF mixture to form a cluster saturated solution. The solvent in the saturated solution was slowly evaporated under air atmosphere, and regular black hexagonal single crystal Ni was obtained in five days. 6 (SCH 2 Ph) 12 .
[0024] Catalyst Ni 6 Preparation of / SiC; Ni 6 The preparation of / SiC samples was completed by a simple rotary evaporation method. The specific process was to add 20 mg of nanocluster Ni 6 The crystals were dissolved in 20 mL of dichloromethane solution and 100 mg of SiC was added. After ultrasonication for 10 minutes, the solution was sealed in a rotary evaporator at 30 °C to completely evaporate the dichloromethane. The obtained solid was then collected and ground to obtain Ni 6 / SiC.
[0025] Catalyst Ni 6 / SiC reduction treatment. Weigh a certain amount of catalyst Ni 6 / SiC added 0.4 mol / L NaBH 4 The solution was ultrasonicated for 2 h, centrifuged at 8000 rpm for 3 min, and then washed with deionized water. This process was repeated four times and dried at 60 °C for 12 h. The obtained catalyst was labeled as Ni 6 / SiC-H. Other metal borohydrides can be used instead of NaBH 4 Preparation of Ni-based nanocluster-supported SiC catalysts with different reduction effects.
[0026] 2) The SiC electrocatalytic material with uniformly loaded Ni clusters prepared by the present invention has high catalytic activity and good stability for hydrogen evolution reaction (HER) catalysts. A new strategy is provided for preparing more Ni-based nanocluster-based electrocatalytic hydrogen production catalysts. Nanoclusters have their own unique advantages in terms of activity, size effect, selectivity and synthesis as hydrogen evolution reaction (HER) catalysts, such as: their high specific surface area and abundant active sites help to improve the activity of hydrogen evolution reaction; due to their small size, the electronic structure and surface activity of nanoclusters may be different from those of large-sized nanoparticles or bulk materials, resulting in the appearance of size effect, thereby improving catalytic performance; nanocluster synthesis technology allows the composition and structure of clusters to be precisely controlled, which helps to optimize catalytic performance; nanoclusters can achieve selective regulation of reactions by regulating the chemical environment of surface active sites, which helps to reduce or avoid the occurrence of side reactions. Therefore, Ni-based nanoclusters with well-defined structures can be synthesized through solvothermal methods, cluster ion chemistry, and other methods, and used as models of HER to regulate catalytic performance and prepare new catalysts. Combined with further theoretical and experimental research, they can be widely used in the field of hydrogen evolution reaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The cluster Ni prepared in Example 1 of the present invention 6 (SCH2Ph) 12 Skeleton structure diagram and single crystal structure diagram (a), UV-Vis spectrum and cluster crystal photo (b).
[0028] Figure 2 The SiC and Ni prepared in Example 1 6 / SiC and Ni 6 XRD patterns of / SiC-H (a), Ni 6 And Ni 6 / SiC and Ni 6 / SiC-H supported Ni 6 UV-visible absorption spectrum dissolved in dichloromethane (b).
[0029] Figure 3 (a) and (b) are respectively the NaBH 4 Sample Ni before treatment 6 / SiC and treated samples Ni 6 TEM images of / SiC-H, (c), (d), and (e) are high-definition images, and (f) and (g) are the corresponding EDS mapping images.
[0030] Figure 4 Ni before reduction obtained in Example 1 6 / SiC and reduced Ni 6The full XPS spectrum of / SiC-H (a), (b), (c), (d), (e) and (f) are the detailed spectra of Ni 2p, O 1s, Si 2p, S2p, and C1s, respectively.
[0031] Figure 5 The SiC and Ni prepared in Example 1 6 / SiC and Ni 6 Polarization curves of / SiC-H (a), 10 mA cm -2 Overpotential under current density (b), Tafel slope (c) and EIS graph at overpotential of 140 mV (d); the electrolyte is 1.0 M KOH.
[0032] Figure 6 Ni prepared in Example 1 6 10-hour constant voltage stability curve of / SiC-H (a) and comparison of polarization curves before and after scanning 1000 cycles (b), the electrolyte is 1.0 M KOH.
[0033] Figure 7 (a) Example 1 obtained is Ni 6 Optimized structure diagram, (b) is the optimized structure diagram of SiC surface partial C replaced by O, (c) is Ni 6 / Optimized structure diagram of SiC-H.
[0034] Figure 8 SiC, Ni 6 / SiC and Ni 6 Calculation results of Gibbs free energy of H adsorption on SiC-H. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.
[0036] Example 1
[0037] This embodiment provides a method for preparing a Ni-based nanocluster-supported silicon carbide water electrolysis hydrogen production catalyst, comprising the following steps:
[0038] (1) Nanocluster Ni 6 (SCH 2 PH) 12
[0039] The preparation process is as follows: First, 2.0 g of NiCl 2 6H 2O and 2.0 g of tetraoctylammonium bromide (TOAB) were dissolved in 300 mL of tetrahydrofuran (THF) to form a dark blue solution; among them, NiCl 2 6H 2 The mass ratio of O and tetraoctylammonium bromide is 1:1, NiCl 2 6H 2 The solubility concentration of O in tetrahydrofuran is 2g / 300ml;
[0040] Add 5.0 mL of toluenethiol (PhCH 2 SH), the resulting solution was stirred for more than 2 hours to ensure that all metal atoms were fully coordinated; then 2 mL of 1 g / mL NaBH 4 The solution quickly turned gray and a dark brown solution was obtained after the reaction was maintained at 10±2℃ for 48 hours, indicating that Ni 6 (SCH 2 Ph) 12 Synthesis of Nanoclusters.
[0041] The dark brown solution was filtered and CH 2 Cl 2 The crude product was dissolved in a mixed solvent of methanol and THF in a volume ratio of 1:1 to form a cluster saturated solution, and placed in an air atmosphere until the solvent evaporated completely to obtain a regular black hexagonal single crystal Ni 6 (SCH 2 Ph) 12 ;
[0042] (2) Catalyst Ni 6 Preparation of SiC
[0043] 20 mg of black hexagonal single crystal Ni 6 (SCH 2 Ph) 12 Dissolve in 20 mL of dichloromethane solution and add 100 mg of SiC. After ultrasonication for 10 minutes, seal the solution in a rotary evaporator at 30 °C to completely evaporate the dichloromethane. Then collect the obtained solid and grind it to obtain Ni 6 / SiC.
[0044] (3) Catalyst Ni 6 / Reduction treatment of SiC
[0045] Weigh 50 mg of catalyst Ni 6 / SiC add 20ml of 0.4mol / L NaBH 4The solution was ultrasonicated for 2 h, centrifuged at 8000 rpm for 3 min, and then washed with deionized water. This process was repeated four times, and dried at 60 °C for 12 h to obtain a Ni-based nanocluster-loaded silicon carbide water electrolysis hydrogen production catalyst, namely Ni 6 / SiC catalyst, labeled as Ni 6 / SiC-H.
[0046] Example 2
[0047] This embodiment provides a method for preparing a Ni-based nanocluster-supported silicon carbide water electrolysis hydrogen production catalyst. The specific steps are referred to Example 1, except that in step (1), "2 mL of NaBH with a concentration of 1 g / mL" is added. 4 Solution" was replaced with "2mL of 1g / mL NaOH solution". The final catalyst was marked as Ni 6 / SiC-H1.
[0048] Example 3
[0049] This embodiment provides a method for preparing a Ni-based nanocluster supported silicon carbide water electrolysis hydrogen production catalyst. The specific steps are referred to Example 1, except that the "20 mL of dichloromethane solution" in step (2) is replaced by "50 mL of dichloromethane solution", and the final catalyst is marked as Ni 6 / SiC-H2.
[0050] Example 4
[0051] The present embodiment provides a method for preparing a Ni-based nanocluster supported silicon carbide water electrolysis hydrogen production catalyst. The specific steps are referred to in Example 1, except that step (3) "centrifuge at 8000 rpm for 3 minutes, wash with deionized water, repeat four times, and dry at 60°C for 12 h" is replaced by "centrifuge at 10000 rpm for 3 minutes, wash with deionized water, repeat four times, and dry at 80°C for 15 h". The catalyst finally obtained is marked as Ni 6 / SiC-H3.
[0052] The intermediate product and the final product of the embodiment were subjected to the following performance tests:
[0053] 1) Cluster Ni 6 Characterization
[0054] The obtained cluster crystals are selected and their structures are first confirmed by single crystal X-ray diffraction. Figure 1 The cluster Ni prepared in Example 1 of the present invention 6 (SCH2Ph) 12 The skeleton structure and single crystal structure diagram (a), UV-Vis spectrum and cluster crystal photo (b). The results show that the four identical Ni6 (SCH 2 Ph) 12 Molecule (abbreviated as Ni 6 )(Z=4) crystallizes in a tetragonal lattice with space group P-421c, and the lattice parameters of the crystal are a=b=19.02 and Ni 6 (SCH 2 Ph) 12 Molecular structure Figure 1 (a), its core structure is composed of 6 nickel atoms, which are arranged in a hexagonal shape. The sulfur atoms are symmetrically distributed above and below the nickel ring plane, and each sulfur atom is coordinated with two nickel atoms. Figure 1 (b) is the UV-visible spectrum of the obtained crystal dissolved in dichloromethane. From the figure, we can see that Ni 6 The characteristic absorption of the cluster is located at 339, 409 and 540 nm. All the results show that the double crown Ni 6 (SCH 2 Ph) 12 The nanoclusters were successfully synthesized.
[0055] 2) Ni 6 Phase characterization of SiC before and after reduction
[0056] Ni 6 The cluster molecules were dissolved in dichloromethane and loaded onto SiC by a simple rotary evaporation method to prepare the catalyst Ni 6 / SiC. It was found that under the action of sodium borohydride, the cluster molecules of SiC samples would leave the thiol ligands and then undergo in-situ transformation. 6 / SiC was treated with sodium borohydride, and the effect of cluster structure change on activity was analyzed by comparing the structural changes and electrocatalytic hydrogen evolution performance of the samples before and after treatment. The obtained samples were characterized by X-ray diffraction and UV-visible spectroscopy. 6 / SiC and Ni 6 The XRD spectrum of the SiC-H sample powder is shown in Figure 2 As shown in (a), it can be seen from the figure that the diffraction peaks of all samples are consistent with the diffraction peaks of the synthesized SiC, and no other impurity diffraction peaks are observed, indicating that Ni 6 The loading of clusters and the subsequent sodium borohydride treatment process have negligible effects on the crystal form of SiC, and the clusters of the loaded samples exist on the surface of SiC in an amorphous form before and after sodium borohydride treatment. 6 Is the structure of Ni stable on the SiC surface? 6 / SiC samples were dispersed in dichloromethane solution to extract the clusters.6 The clusters are soluble in dichloromethane solution. The insoluble SiC support is removed by centrifugation, and the obtained supernatant shows the same 6 The solution formed by dissolving the cluster into dichloromethane solution has the same color. 6 And Ni 6 / SiC and Ni 6 / SiC-H supported Ni 6 The solution obtained by dissolving in dichloromethane was analyzed by UV-visible absorption spectroscopy and compared with the UV spectrum of the cluster solution with the theoretical loading concentration. Figure 2 (b) shows the peak position of the obtained solution and Ni 6 The clusters are consistent, indicating that the cluster structure has not changed after loading. The corresponding UV absorption of the sample after sodium borohydride treatment is significantly lower than that before treatment, indicating that the cluster structure may have changed as expected.
[0057] In order to understand your 6 The cluster structure transformation process of / SiC samples before and after sodium borohydride reduction treatment was analyzed by transmission electron microscopy. The results are shown in Figure 2. Figure 3 As shown, (a) and (b) are respectively the NaBH 4 Sample Ni before treatment 6 / SiC and treated samples Ni 6 TEM images of / SiC-H, (c), (d), (e) are high-definition images, and (f) and (g) are corresponding EDS mapping images. Figure 3 It can be seen that the morphology of SiC loaded with clusters is basically the same as that of pure SiC and still exists mainly in the form of nanoparticles and nanowires. This is because the cluster Ni 6 In the amorphous state, the transmission electron microscope cannot effectively image it. Combined with the TEM-mapping image, it can be seen that the local agglomeration of nanoclusters is because the SiC nanoparticles are more likely to deposit clusters than nanowires ( Figure 3 (a)). The catalytic sample Ni 6 The TEM image of / SiC-H shows that nanoparticles appear on the surface of the carrier, and the corresponding dark field TEM image shows that sub-nano particles and single atoms appear on the surface of the carrier ( Figure 3 (e)), combined with TEM-mapping, it shows that the Ni element is evenly distributed on the surface of SiC ( Figure 3 (f)), which indicates that the cluster structure has changed and Ni has a new existence form.
[0058] In order to further understand the effect of sodium borohydride treatment on the cluster structure, Ni 6The SiC loaded samples were subjected to XPS analysis. Figure 4 Ni before reduction obtained in Example 1 6 / SiC and reduced Ni 6 / SiC-H full XPS spectrum, (a), (b), (c), (d), (e) and (f) are the detailed spectra of Ni 2p, O 1s, S2p, C 1s and Si 2p respectively. Figure 4 As shown in (a), the characteristic signals of Si, Ni, S, C and O can be observed in the full XPS spectra of both samples, which means that these five elements coexist on the sample surface. 4 The treated samples (Ni 6 / SiC-H) has a significantly lower peak intensity than before treatment, and the S2p signal almost disappears, indicating that the cluster structure of the sample has lost a certain degree of damage after being treated with sodium borohydride. The Ni 2p fine spectrum results show that when not treated with sodium borohydride, its corresponding characteristic signals are located at 870.51eV (2p 1 / 2) and 853.24eV (2p 3 / 2), corresponding to the +2-valent Ni coordinated with S in the cluster structure. 4 After treatment, the Ni signal in the obtained sample becomes complex. The results of peak fitting show that in addition to a group of signals at 870.51eV (2p 1 / 2) and 853.24eV (2p 3 / 2) that can be attributed to +2-valent Ni coordinated with S atoms, there is also a group of characteristic signals at 872.76eV (2p 1 / 2) and 855.49eV (2p 3 / 2). Compared with the previous group of signals, this signal is blue-shifted by about 2.2eV as a whole, and it is attributed to Ni atoms bonded to O in an amorphous state. This attribution is further confirmed by the peak fitting results of the 2p spectrum of O. Figure 4 As shown in (c), the 2p signal of O after sodium borohydride treatment shows obvious broadening and can be fitted into two groups of characteristic signals, one group located at 532.7eV and belonging to the signal of O element coordinated with Ni; the other group is located at the signal of O element coordinated with Si atoms. Among them, the latter has a red shift of about 0.3eV compared with the sample not treated with sodium borohydride, which may be caused by the local reduction of SiC surface by sodium borohydride. This red shift is also confirmed in the peak fitting results of Si 2p spectrum, as shown in Figure 2. Figure 4 As shown in (d), the Si signal at 101.41 eV before treatment, which belongs to O coordination, moves to 100.75 eV after sodium borohydride treatment, showing a red shift of 0.6 eV, which further illustrates the local reduction of the SiC surface by sodium borohydride. At the same time, it is observed that the 2p signal of S does not move significantly before and after sodium borohydride treatment, but the 2p signal of S becomes weaker after treatment, which indicates that the cluster is partially deconstructed after treatment. This is combined with the signal of C in the sample, such as Figure 4 As shown in (e), the signal at 283.86 eV belonging to C coordinated with H before treatment becomes weaker after sodium borohydride treatment, which further indicates that part of the organic ligands on the surface of the clusters are removed by sodium borohydride. Another group of C element signals at 282.48 eV belonging to Si coordination become stronger after treatment, and a 0.5 eV blue shift occurs, which indicates that after the clusters loaded on the SiC surface are removed, the SiC as a carrier is exposed. Based on the above characterization, the following conclusions are drawn: Ni 6 SiC-loaded samples (Ni 6 After the Ni / SiC) clusters were treated with sodium borohydride, 6 The organic ligands on the surface are partially removed, and the Ni atoms combine with the O on the SiC surface to form NiO x Deposited on SiC support. According to a series of characterization results, it is confirmed that Ni 6 NaBH for SiC 4 After treatment, the cluster structure changed, some clusters decomposed, and a new substance NiO was formed. x .
[0059] 3) Evaluation of electrocatalytic hydrogen evolution performance
[0060] To determine the use of NaBH 4 After treatment, the effect of cluster structure change on the catalytic activity of the material was studied. 6 / SiC and Ni 6 / SiC-H materials were made into working electrodes and their electrocatalytic hydrogen evolution performance was evaluated. Figure 5 (a) SiC, Ni 6 / SiC and Ni 6 / SiC-H in 1.0M KOH solution. From the figure, we can see that SiC, Ni 6 / SiC and Ni 6 / SiC-H all showed certain activity, but there were obvious differences in activity. Figure 5 (b) SiC, Ni 6 / SiC and Ni 6 / SiC-H at 10mAcm -2 Overpotential under current density, using the sample Ni treated with sodium borohydride 6 / SiC-H at a current density of 10 mA cm -2 The required overpotential is 93 mV, while the untreated sample Ni 6 / SiC requires 142mV, and pure SiC requires 292mV. Figure 5The linear part of the polarization curve in (a) is fitted using the Tafel formula (η = b log (j) + a), and the fitted value is the Tafel slope, which helps reveal the electrocatalytic activity, such as Figure 5 As shown in (c), Ni 6 / SiC-H has the smallest Tafel slope of 340mV dec -1 , and Ni 6 / SiC needs to reach 387mV dec -1 , SiC is even higher, reaching 602mV dec -1 , indicating that in Ni 6 / SiC-H surface hydrogen evolution reaction is easier to proceed. The Tafel slope of the prepared catalyst is 300mV dec -1 The above shows that the hydrogen evolution reaction process is mainly carried out through Volmer-Heyrovsky. In order to further study the catalyst interface mass transfer resistance, the sample was tested by EIS under the condition of 100mV overpotential. Figure 5 (d) As shown in the figure, in the charge transfer resistance obtained by fitting in the low frequency region, SiC is the smallest, while Ni 6 / SiC is the largest, and Ni 6 / SiC-H resistance decreases. The reason for this is that the cluster Ni 6 The surface is wrapped by organic ligands, and the conductivity is poor. After treatment with sodium borohydride, part of the cluster structure is destroyed, Ni is exposed, and the conductivity becomes better, but the presence of O leads to the formation of NiO x , but at the same time there are still some clusters remaining, which also leads to the conductivity not being significantly improved, and the overall performance is still lower than SiC.
[0061] 4) Ni 6 / SiC-H Catalytic Stability
[0062] In addition to HER activity, stability is another important indicator for evaluating the HER performance of materials. Figure 6 Ni prepared in Example 1 6 The 10-hour constant voltage stability curve of / SiC-H (a) and the comparison of polarization curves before and after scanning 1000 cycles (b), the electrolyte is 1.0M KOH. Figure 6 (a) shows that the potential is 93 mV and the current density is 10 mA cm -2 When the current density decay is not obvious, it can be seen that Ni 6 / SiC-H showed good catalytic activity and stability in alkaline solution. Figure 6 (b) is Ni 6Polarization curves of the SiC-H / SiC-H sample before and after scanning 1000 cycles in the potential range of -1.0 to 1.0 mV vs. RHE. The polarization curves changed before and after the test, indicating that the catalyst itself may have changed, which is related to the incomplete conversion of the clusters.
[0063] In order to verify the experimental results and better understand Ni 6 / SiC-H and Ni 6 / SiC in the HER process, we will 6 The system of / SiC is simplified as follows: Ni 6 The flat plate model of the molecule, in the process of participating in HER, is actually the surface cluster Ni 6 Participate in the reaction, further simplified to Ni 6 ,like Figure 7 (a). From the calculations in Chapter 2, we know that the surface of the optimized structure of the SiC (001) plane with exposed C atoms still has a small amount of O, so we optimized the surface structure, replaced part of the C with O atoms, and constructed O-terminated SiC, as shown in Figure 7 (b) NaBH 4 The treated samples, as shown by TEM and XPS characterization results, have a partially disintegrated cluster structure, and Ni and O on the SiC surface are combined, which can be simplified into a SiC-O-Ni structure, such as Figure 7 (c). On this basis, we established a model for H adsorption ( Figure 8 ), and compare the Gibbs free energy of hydrogen adsorption (ΔG H* ) size. According to previous literature, the Gibbs free energy of hydrogen adsorption (ΔG H* ) is considered to be the key parameter to describe HER activity. According to the Sabatier principle, ΔG H* It should be close to 0 eV to be an efficient HER electrocatalyst. H* Due to the high binding strength between hydrogen atoms and the catalyst, the rate of hydrogen atoms releasing from the catalyst surface is slowed down. H* The proton / electron transfer step becomes an endothermic process, the catalyst has poor binding force with hydrogen atoms, and is not conducive to the catalytic reaction. Figure 8 As shown, the ΔG of SiC H* The value is 1.1eV, while Ni 6 / SiCΔG H* The higher value is 1.3eV, which indicates that after loading the clusters, the clusters cover the original SiC active sites, which reduces the hydrogen adsorption-desorption capacity, which is consistent with the CV results. 6 ΔG of SiC-H H* Almost 0, indicating that the catalyst Ni6 / SiC-H has better hydrogen adsorption-desorption characteristics, and the hydrogen atom desorption ability of the Heyrovsky step is optimized, thereby improving the HER performance.
[0064] 5) Electrochemical performance test
[0065] All electrochemical data were tested using a Coster CS350M electrochemical workstation. The electrolytic cell was a double-chamber H-type electrolytic cell with good airtightness. The cathode chamber and the anode chamber were separated by a proton exchange membrane (Nafion 117). The catalyst was dropped on carbon paper as the working electrode, the Pt mesh electrode was used as the counter electrode, the calomel electrode was used as the reference electrode, and 1.0M KOH solution was used as the electrolyte. All applied potential values were converted to relative reversible hydrogen electrodes:
[0066] E(RHE)=E(SCE)+0.241+0.0592*pH (1)
[0067] Linear sweep voltammetry (LSV) was used to obtain polarization curves between 1.0 and -1.5 V (relative to RHE) at a scan rate of 10 mV / s. Electrochemical impedance spectroscopy (EIS) was performed in the frequency range of 100 kHz to 0.1 Hz with an AC amplitude of 10 mV. Cyclic voltammetry (CV) was performed between 0.2 and 0.4 V (relative to the reference electrode) at a scan rate of 5 to 100 mV / s. The current density difference and CV scan rate were plotted, and half of the slope value obtained by linear fitting was used to estimate the electrochemical double layer capacitance (C dl ). Specifically, as shown in formula (2):
[0068] C dl =Δj / 2v (2)
[0069] In addition, the LSV curves in this work were iR-corrected according to the formula. iR-校正 =E-iR, where E is the measured potential, R is the solution resistance, i is the corresponding current, and E iR-校正 This is the final potential after iR correction.
[0070] The preparation process of the working electrode is as follows: weigh 3.0 mg of the above-prepared sample into a test tube, add 300 μL of anhydrous ethanol and 20 μL of Nafion into the test tube respectively, ultrasonically disperse for 30 minutes to form a uniform slurry, and then use a pipette to transfer 100 μL of the slurry and drop it on the surface of carbon paper with a diameter of 1.0 cm×1.0 cm, and dry it naturally for use.
[0071] By treating the product Ni of Example 2-4 6 / SiC-H1、Ni 6 / SiC-H2、Ni 6 / SiC-H3 was studied by XRD and UV spectroscopy. The catalysts prepared in Examples 2-4 were similar to the catalyst Ni prepared in Example 1. 6 / SiC-H have exactly the same structure, indicating that the change of conditions in Examples 2-4 does not affect Ni 6 / SiC-H preparation, and also proved that Ni 6 The preparation conditions of / SiC-H catalyst are relatively simple and easy.
[0072] Those skilled in the art should understand that the above are only some specific embodiments of the present invention, rather than all embodiments. It should be noted that for those of ordinary skill in the art, many modifications and improvements can be made, and all modifications or improvements that do not exceed the scope of protection of the present invention should be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a Ni-based nanocluster-supported silicon carbide water electrolysis hydrogen production catalyst, characterized in that: The steps include: S1, dissolving Ni salt and tetraoctylammonium bromide TOAB in tetrahydrofuran (THF) at a mass ratio of 1:2-2:1 to form a dark blue solution; wherein the concentration of Ni salt in tetrahydrofuran is 0.004-0.01 g / ml; S2. Take 300 ml of dark blue solution, add 4-6 ml of toluene mercaptan PhCH2SH, stir thoroughly until all metal atoms are fully coordinated, slowly drop borohydride solution or hydroxide solution until the solution turns gray, stop adding, keep the reaction at 10±2℃ for 48-72h, and obtain Ni6(SCH2Ph) 12 Dark brown solution of nanoclusters; S3, the dark brown solution was filtered, and the filtered material was washed to obtain a crude product; the crude product was dissolved in a mixed solvent of methanol and THF in a volume ratio of 1:1 to form a cluster saturated solution, and the solution was placed in an air atmosphere until the solvent was completely evaporated to obtain a regular black hexagonal single crystal Ni6(SCH2Ph) 12 ; S4, black hexagonal single crystal Ni6 (SCH2Ph) 12 Dissolved in dichloromethane solution, then added SiC ultrasonic dispersion to obtain a mixed solution, black hexagonal single crystal Ni6(SCH2Ph) 12 The mass ratio of Ni6 to SiC is 1:(4-6); then the dichloromethane in the mixed solution is completely evaporated, the obtained solid is collected and ground to obtain Ni6 / SiC; S5. Add Ni6 / SiC to a NaBH4 solution with a concentration of 0.35-0.45 mol / L in an amount of 2.5-4 mg / ml, perform ultrasonication, separation, washing and drying to obtain a Ni-based nanocluster-loaded silicon carbide water electrolysis hydrogen production catalyst, which is recorded as Ni6 / SiC-H catalyst.
2. The method for preparing the Ni-based nanocluster supported silicon carbide water electrolysis hydrogen production catalyst according to claim 1, characterized in that: The Ni salt is NiCl2·6H2O.
3. The method for preparing the Ni-based nanocluster supported silicon carbide water electrolysis hydrogen production catalyst according to claim 1, characterized in that: The borohydride solution is a sodium, potassium or lithium borohydride solution, and the hydroxide solution is a sodium, potassium or lithium hydroxide solution.
4. The method for preparing the Ni-based nanocluster-supported silicon carbide water electrolysis hydrogen production catalyst according to claim 1 or 3, characterized in that: The concentration of the borohydride solution or hydroxide solution is 0.9-1.1 g / ml.
5. The method for preparing the Ni-based nanocluster supported silicon carbide water electrolysis hydrogen production catalyst according to claim 1, characterized in that: In step S3, the dark brown solution is filtered with absorbent cotton.
6. The method for preparing the Ni-based nanocluster supported silicon carbide water electrolysis hydrogen production catalyst according to claim 1, characterized in that: In step S3, CH2Cl2 and water are added to wash the filtered product to obtain a crude product.
7. The method for preparing the Ni-based nanocluster supported silicon carbide water electrolysis hydrogen production catalyst according to claim 1, characterized in that: Black hexagonal single crystal Ni6(SCH2Ph) in step S4 12 The solubility concentration in dichloromethane solution is 0.8-1.2 mg / ml.
8. The method for preparing the Ni-based nanocluster supported silicon carbide water electrolysis hydrogen production catalyst according to claim 1, characterized in that: In step S4, the mixed solution is sealed in a rotary evaporator at 30-40° C. to completely evaporate the dichloromethane.
9. The method for preparing the Ni-based nanocluster supported silicon carbide water electrolysis hydrogen production catalyst according to claim 1, characterized in that: In step S5, the product is separated by ultrasonication for 2-3 hours, centrifugation at 8000-10000 rpm for 3-5 minutes, washed four times with deionized water, and dried at 60-80° C. for 12-15 hours.
10. A Ni-based nanocluster-supported silicon carbide catalyst for electrolyzing water to produce hydrogen, obtained by the method for preparing the Ni-based nanocluster-supported silicon carbide catalyst for electrolyzing water to produce hydrogen according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of ultra-small nickel-iron nanoclusters and ultra-small nickel-iron nanoclusters
CN111842919A
Nickel modified carbonized wood / sulfide heterojunction composite electrocatalyst as well as preparation method and application thereof
CN114836784A
Platinum alloy cluster catalyst as well as preparation method and electro-catalysis application thereof
CN118173806A
Gold-doped nickel nanocluster, preparation method therefor, and use thereof
WO2022010306A1
KR20230161656A